Interaction of Zn with ferrihydrite and its cooperative binding in the presence of PO4. (1st March 2022) - Van Eynde, Elise; Hiemstra, Tjisse; Comans, Rob N.J.
Abstract: In nature, zinc (Zn) ions interact with natural organic matter and soil metal (hydr)oxides. The resulting solid-solution partitioning is of major importance for the geochemical cycling and environmental risks of toxicity and deficiency. Ferrihydrite (Fh) is an important proxy for the natural metal (hydr)oxide fraction in soils. At its surfaces, Zn 2+ ions have multi-component interactions, for instance with phosphate (PO4 3− ). In nature, the latter is particularly relevant in topsoils since PO4 is omnipresent and has a high affinity for Fh. Zinc and phosphate ions may bind cooperatively by electrostatic forces and/or by ternary complex formation. This was studied presently with batch adsorption experiments using freshly prepared and well-characterized Fh nanoparticles. The data have been interpreted using the charge distribution (CD) model combined with a surface structural model for Fh that includes site heterogeneity. The CD coefficients have been derived independently by optimization of the surface geometries with molecular orbital calculations applying density functional theory (MO/DFT/B3LYP/6-31+G**). These computations confirm that upon adsorption Zn can change spontaneously its coordination number from 6 to 4. In agreement with literature results from X-ray absorption spectroscopy (XAS), Zn is bound at low loading as a double-corner bidentate complex. At higher loading, the number of ions in the second shell of Zn decreases according to published XAS results. Our model with the formation of surface complexes with single corner-sharing can quantitatively predict this decrease. Zn polymerization only occurs at a very high molar Zn/Fe ratio (>0.1), which can be described using a neutral, hydrolyzed Zn-dimer species. The presence of PO4 enhances the Zn adsorption, especially in the pH range 5–6. At the Zn and PO4 levels studied, no ternary Zn-P surface complexes can be revealed. For comparison, we re-interpreted copper (Cu)-PO4 -Fh adsorption literature data with similar metal and PO4 loadings. In line with the results for Zn, no ternary Cu-P surface complexes were found. We conclude that electrostatic interactions explain metal adsorption at background levels in multi-component systems, and that ternary complexes may form only at rather extreme metal or PO4 loading conditions.